Analisis Putusan Hak Asuh Anak Bersama Pasca Perceraian Perspektif Kongres Ulama Perempuan Indonesia (KUPI) - Sabila, Awwalia Indah; Musfiroh, Mayadina Rohmi; Rosyada, Amrina (Universitas Batanghari Jambi, 2025)
This research discusses court decisions regarding joint custody of children after divorce with a maslahat approach based on the nine basic values of the Indonesian Women's Ulama Congress (KUPI). The main issue raised is how the application of joint custody can ensure the best interests of the child, particularly in reducing the negative emotional impact of divorce, as well as ensuring the involvement of both parents in the child's life. The purpose of this study is to evaluate the appropriateness of Banjarbaru Religious Court Decision Number 369/Pdt.G/2017/PA.Bjb. which grants primary custody to the father but still gives the mother the opportunity to interact with the child on weekends. The analysis in this study is based on the theory of maslahat, which prioritizes the best interests of children, as well as the nine basic values of KUPI, namely equality, equality, justice, humanity, nationality, universality, divinity, mercy, and benefit. Using the juridical-normative method, this research analyzes court decisions, legal regulations, and related theories. The results show that the concept of joint custody supports the best interests of children, reduces the negative psychological impact of divorce, and improves children's welfare through the involvement of both parents.